Analisis Proses Penanganan Cargo Perishable Goods Pada Operasional Kargo Udara Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Yunus Purnama; Vidyana Mandrawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In air transportation activities, the cargo unit is very important because it is responsible for the smooth process of delivering goods, especially perishable items that require special care due to their fragile nature. The purpose of this research is to evaluate the handling process of perishable goods and to identify various obstacles faced by the staff while conducting operations at one of air cargo companies at Jenderal Ahmad Yani Airport Semarang. The research method used is a qualitative method with data collection techniques in the form of observation, interviews, and documentation. Data collection was conducted through interviews with officers directly involved in cargo operational activities, supported by field observations and documentation during the research period, namely February–June 2026. The research results show that the handling of perishable cargo includes the stages of receipt, document and physical inspection of goods, storage according to characteristics, loading coordination with airlines, and loading onto the aircraft. The obstacles that arise include delayed or changed flight schedules, limited cooling space, incorrect sender documents, and bad weather. To address this, the company continues to coordinate with airlines, prioritize cooling facilities, enhance the accuracy of document verification, and adjust operational procedures to ensure the quality of the cargo is maintained until delivery is complete.